2020
DOI: 10.1017/dce.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Roughness-induced vehicle energy dissipation from crowdsourced smartphone measurements through random vibration theory

Abstract: We propose, calibrate, and validate a crowdsourced approach for estimating power spectral density (PSD) of road roughness based on an inverse analysis of vertical acceleration measured by a smartphone mounted in an unknown position in a vehicle. Built upon random vibration analysis of a half-car mechanistic model of roughness-induced pavement–vehicle interaction, the inverse analysis employs an L2 norm regularization to estimate ride quality metrics, such as the widely used International Roughness Index, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…With the rapid development of smartphones in recent years, the technology of road detection using the built-in sensors of smartphones has become an important supplement to road pothole detection. Many studies have demonstrated that the built-in accelerometers of mobile phones can be used to detect road anomalies [7,13,15]. Vaiana et al, investigated young drivers' driving behavior on horizontal curves, by analyzing speed and acceleration data collected via smartphones.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of smartphones in recent years, the technology of road detection using the built-in sensors of smartphones has become an important supplement to road pothole detection. Many studies have demonstrated that the built-in accelerometers of mobile phones can be used to detect road anomalies [7,13,15]. Vaiana et al, investigated young drivers' driving behavior on horizontal curves, by analyzing speed and acceleration data collected via smartphones.…”
Section: Related Workmentioning
confidence: 99%
“…Gillespie et al [29] were the first to develop methods for the indirect detection of road anomalies. Botshekan et al [13] estimated road roughness from the power spectral density (PSD) of acceleration, based on stochastic vibration analysis of a semi-vehicle mechanical model of roughness-induced road-vehicle interaction, and demonstrated that the location of the mobile phone in the vehicle only slightly affects the detection of road roughness. On the basis of using the PSD of acceleration to reflect the road profiles, Daraghmi et al [7] used blind source separation technology to separate the vehicle model from the measurement of acceleration, so as to reduce the influence of the vehicle model on the detection results.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation